2010
DOI: 10.1111/j.1574-6968.2010.01972.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergistic interactions of the effects of various statins and azoles against some clinically important fungi

Abstract: The treatment of opportunistic fungal infections is often difficult as the number of available antifungal agents is limited. Nowadays, there is increasing interest in the investigation of the antifungal activity of nonantifungal drugs, and in the development of efficient antifungal combination therapy. In this study, the in vitro interactions of the effects of various statins (lovastatin, simvastatin, fluvastatin, atorvastatin (ATO), rosuvastatin (ROS) and pravastatin) and various azole antifungals [miconazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 33 publications
1
54
0
Order By: Relevance
“…In a study conducted with strains of C. albicans and C. glabrata, evaluating the synergism between simvastatin and fluconazole, an additive effect was observed 9 . In our study, the results were different; we found a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted with strains of C. albicans and C. glabrata, evaluating the synergism between simvastatin and fluconazole, an additive effect was observed 9 . In our study, the results were different; we found a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin (Sigma-USA) was activated in an ethanol solution of NaOH (15% (vol/vol) and 0.25% (m/vol) NaOH) at 60 °C for one hour 9 . The simvastatin solution was filtered and placed in a desiccator for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several statins, especially simvastatin and fluvastatin, were seen to act synergistically with various antifungals, showing strong fungicidal effects in vitro [67,68]. …”
Section: Pleiotropic Effects Of Statinsmentioning
confidence: 99%
“…The MIC determinations vary between different laboratories but are generally in the micromolar range (lowest is 0.4 mg/ml or 0.9 mmol/l). The synergistic effect of statins together with different standard antifungal drugs has also been evaluated [30][31][32][33][34][35][36][37][38][39], and the MIC is then generally lowered, sometimes by as much as with a factor of 10. Two articles report on potent synergistic effects of statins in combination with the atypical drugs primycin [40] and suramin [41] against various moulds.…”
Section: The Clinical Problem: Fungal Infectionsmentioning
confidence: 99%